Analisis Efisiensi Energi Motor Induksi pada Horizontal Pumping System dengan Penggunaan Variable Speed Drive - Ida Bagus Made Wisnu Wardana Wisnu; M. Saleh Al Amin; Nita Nurdiana (Teknik Elektro, Universitas Muhammadiyah Palembang, 2026)
Induction motors are the primary drivers in various industrial systems; however, their high energy consumption poses a challenge to efficiency improvement efforts. One technology used to optimize energy consumption is the Variable Speed Drive (VSD), which allows motor speed to be adjusted according to load requirements. This study aims to analyze the effect of using a VSD on the energy efficiency of a three-phase induction motor in a horizontal pumping system for produced water injection. Field tests were conducted on a 185 kW induction motor controlled by a VSD with frequency variations of 45–47.5 Hz. Parameters measured included voltage, current, power factor, fluid pressure, flow rate, and hydraulic output power. System efficiency was calculated as the ratio between electrical input power and hydraulic output power. The results show that the use of a VSD reduced starting power from 923.07 kW to 65.06 kW and increased efficiency from 57.26% to 59.34%. In conclusion, the VSD not only improves energy efficiency but also reduces mechanical load, stabilizes operation, and extends equipment lifespan. The implementation of this technology is recommended for industrial pump systems with variable torque loads to support energy conservation.